Insulin-like growth factor-binding protein 7 (IGFBP7): A microenvironment-dependent regulator of angiogenesis and vascular remodeling - Lit, Kwok Keung; Zhirenova, Zhamilya; Blocki, Anna (Frontiers in Cell and Developmental Biology, 2024)
Insulin-like Growth Factor-Binding Protein 7 (IGFBP7) is an extracellular matrix (ECM) glycoprotein, highly enriched in activated vasculature during development, physiological and pathological tissue remodeling. Despite decades of research, its role in tissue (re-)vascularization is highly ambiguous, exhibiting pro- and anti-angiogenic properties in different tissue remodeling states. IGFBP7 has multiple binding partners, including structural ECM components, cytokines, chemokines, as well as several receptors. Based on current evidence, it is suggested that IGFBP7’s bioactivity is strongly dependent on the microenvironment it is embedded in. Current studies indicate that during physiological angiogenesis, IGFBP7 promotes endothelial cell attachment, luminogenesis, vessel stabilization and maturation. Its effects on other stages of angiogenesis and vessel function remain to be determined. IGFBP7 also modulates the pro-angiogenic properties of other signaling factors, such as VEGF-A and IGF, and potentially acts as a growth factor reservoir, while its actual effects on the factors’ signaling may depend on the environment IGFBP7 is embedded in. Besides (re-)vascularization, IGFBP7 clearly promotes progenitor and stem cell commitment and may exhibit anti-inflammatory and anti-fibrotic properties. Nonetheless, its role in inflammation, immunomodulation, fibrosis and cellular senescence is again likely to be context-dependent. Future studies are required to shed more light on the intricate functioning of IGFBP7.